9 Square in the Air: Not Your Parents' Traditional Four Square Game. (4th May 2018) - Hanson, Amber Hall; Barney, David
Abstract : Physical educators are constantly looking for new ideas and activities that will quickly grab the interest of their students. 9 Square in the Air is a game that does just this. The game was developed as a way to integrate students who enjoy volleyball and those who like Four Square. 9 Square in the Air provides the opportunity for students to use many common game skills (i.e., hand-eye coordination, passing, strategizing, defense), while simultaneously learning to cooperate and resolve conflict. This article examines the game, the rules, and implementation and benefits of 9 Square in the Air in physical education. Teachers will also find tips for implementing this game at all levels and drills that will help their students find increasing success. Readers will find that this game embraces many concepts of the comprehensive school physical activity program as well as the National Standards for physical education. Finally, a simple case study depicts exactly how one elementary school implemented 9 Square in the Air and the result of the game in the attitudes and activity of students.